The Municipal Map in Spain: Structure, Evolution and Issues - Albet i Mas, Abel (Geopolítica(s). Revista de estudios sobre espacio y poder, 2019)
The Spanish municipal map shows serious dysfunctions (persistence of small municipalities in population and on surface, enclaves and problematic boundaries, over-sized attributions) consequence of a tradition that refuses to change. After an analysis of the evolution and the current structure of the legislation on the municipal map and its changes, the text denounces the great difficulties and reluctance to carry out a systematic review of the municipal map. Local administration is challenged to differentiate the “political” territory —as the place for citizen’s identity and participation but, I fact, becoming a fief of influence for political parties—, from the “management” territory —as the most suitable for an operational local public administration in order to guarantee the welfare and quality of life for the population—. The first step of the reform should be a review of the municipal attributions, capabilities and finances, establishing those that can be assigned to other administrations.